2006
DOI: 10.1016/j.jpain.2005.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Child Anxiety Sensitivity: Relationship to Children’s Experimental Pain Responsivity

Abstract: The present study highlights sex differences in the links among parent and child anxiety sensitivity (fear of anxiety sensations) and children's experimental pain responses. Among girls, childhood learning history related to somatic symptoms may be a particularly salient factor in the development of anxiety sensitivity and pain responsivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
35
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 29 publications
7
35
3
Order By: Relevance
“…As with any behavior as complex as pain behavior, the emergence of sex differences in pain after puberty probably results from a dynamic interplay of biologic, 8,22,26 psychological, 15,38 sociocultural, 3,27 and developmental 21,39 factors across childhood and adolescence. Research on developmental factors in gender stereotypes suggests concepts of maleness are more stereotypically framed than concepts of femaleness, 17 boys are punished more often than girls for departing from gendernormative behavior, 6,[10][11][12]19,36 and polarized views of gender increase as young people move through adolescence, with masculinity more strongly connoting the absence of femininity and vice versa.…”
mentioning
confidence: 99%
“…As with any behavior as complex as pain behavior, the emergence of sex differences in pain after puberty probably results from a dynamic interplay of biologic, 8,22,26 psychological, 15,38 sociocultural, 3,27 and developmental 21,39 factors across childhood and adolescence. Research on developmental factors in gender stereotypes suggests concepts of maleness are more stereotypically framed than concepts of femaleness, 17 boys are punished more often than girls for departing from gendernormative behavior, 6,[10][11][12]19,36 and polarized views of gender increase as young people move through adolescence, with masculinity more strongly connoting the absence of femininity and vice versa.…”
mentioning
confidence: 99%
“…In brief [14][15][16], after completing questionnaires, children participated in a series of tasks that involved self-report and behavioral responses to cold, pressure, and heat tasks, with the order of tasks counterbalanced. The three tasks involved immersing the hand in cold water, applying pressure using a weighted lucite point to the finger, and holding the forearm over a radiant heat diode.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited through mass mailings, posted advertisements, and classroom presentations. Participants were part of a larger study exploring laboratory pain responses in healthy children [14][15][16].…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several parental factors have been highlighted that may have an impact on their children's anxiety, such as parental anxiety, modelling, negative information transmission, and parental behaviours such as overprotection (e.g., Creswell, Murray, Stacey, & Cooper, 2011;Rapee, 2012). Concerning parental AS, however, mixed results have been obtained: some authors have observed a significant link between parental and child AS (e.g., East, Berman, & Stoppelbein, 2007;Tsao et al, 2005Tsao et al, , 2006, while others have not (e.g., Drake & Kearney, 2008;Silverman & Weems, 1999;van Beek, Perna, Schruers, Muris, & Griez, 2005). Other investigations have focused on the impact of learning experiences within the family environment (Stewart et al, 2001;Watt et al, 1998).…”
mentioning
confidence: 99%